2008
DOI: 10.4049/jimmunol.180.11.7687
|View full text |Cite
|
Sign up to set email alerts
|

No Advantage of Cell-Penetrating Peptides over Receptor-Specific Antibodies in Targeting Antigen to Human Dendritic Cells for Cross-Presentation

Abstract: Induction of CTL responses by dendritic cell (DC)-based vaccines requires efficient DC-loading strategies for class I Ags. Coupling Ags to cell-penetrating peptides (CPPs) or receptor-specific Abs improves Ag loading of DCs. In contrast to CPPs, receptor-specific Abs deliver conjugated Ags to DCs with high specificity, which is advantageous for in vivo strategies. It has, however, been speculated that CPPs facilitate uptake and endosomal escape of conjugated Ags, which would potently enhance cross-presentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…Notwithstanding, it has been shown before by our group as well as others that antigens targeted to the CRD of DC-SIGN can also be cross-presented, despite the fact that they are routed to lysosomal compartments. 8,10 Possibly, targeting the CRD-domain routes part of the antigen toward a recently defined antigen storage compartment distinct from early endosomal and MHC class II loading compartments. This storage compartment stains positive for the lysosomal marker LAMP1, negative for MHC classes I and II, and (green) at 4°C, washed, and shifted at 37°C for the indicated time points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notwithstanding, it has been shown before by our group as well as others that antigens targeted to the CRD of DC-SIGN can also be cross-presented, despite the fact that they are routed to lysosomal compartments. 8,10 Possibly, targeting the CRD-domain routes part of the antigen toward a recently defined antigen storage compartment distinct from early endosomal and MHC class II loading compartments. This storage compartment stains positive for the lysosomal marker LAMP1, negative for MHC classes I and II, and (green) at 4°C, washed, and shifted at 37°C for the indicated time points.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 By analogy, vaccination strategies targeting antigens to the CRD of DC-SIGN resulted in antigen presentation via MHC classes I and II. [7][8][9][10] In vivo, targeted delivery of antigens to the CRD of DC-SIGN in Rag2 Ϫ/Ϫ ␥C Ϫ/Ϫ mice reconstituted with human immune cells also induced antigen-specific T-cell responses. 11 Thus far, both antibodies and sugar ligands have been exploited to target antigens to the CRD of DC-SIGN.…”
mentioning
confidence: 99%
“…Draining lymph node CD11c + DCs from mice cross presented OVA 48 h after injection of 3D8-OVA [250][251][252][253][254][255][256][257][258][259][260][261][262][263][264] . Ag targeting to the cross-presentation pathway in DCs has been studied using Ags coupled to carriers such as cell-penetrating peptides (CPPs) (27)(28)(29), endocytosed Hsps (9,30), and Abs against DC-specific endocytic receptors, including DC-SIGN and DEC205 (26). In particular, Ag targeting to the cross-presentation pathway in both murine and human DCs has been extensively studied by Steinman's group, using an anti-DEC205 Ab (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, they are also called protein transduction domain (PTD) reflecting their origin as occurring in natural proteins. Recently, a study comparing three different CPPs (including TAT and polyR) with the antibody against the DC receptor SIGN demonstrated that polyR is more potent than TAT to deliver protein to DCs and that similar antigen presentation was achieved by DCs loaded with either polyR or the anti-DC-SIGN antibody, at least in vitro (14). Therefore, the interest remains very high to identify a CPP allowing efficient multi-epitopic antigen delivery for cancer immunotherapies.…”
Section: Introductionmentioning
confidence: 99%